PENGARUH POLA TANAM TEKNIK VERTIKULTUR TERHADAP PERTUMBUHAN DAN HASIL UBI JALAR (Ipomoea batatas L.) VARIETAS SUKUH - muhammad zakaria yahya (AGRONISMA, 2021)
Sweet potato is an alternative food that can be used for food and industry (flour, starch, and dye), especially the sukuh variety (white tubers) which has a high starch yield. The more limited urban land and the narrowness of the village land, there is a need for verticulture techniques. This study was conducted to determine how the growth and yield of sweet potato varieties of Sukuh on the effect of cropping patterns with verticulture techniques. This study used a single factor randomized block design with treatment as a group consisting of 7 treatments, namely cropping patterns (P1, P2, P3, P4, P5, P6, P7). The results showed that the growth of the P1 cropping pattern had the highest value on the parameters of plant length, number of leaves and on yield parameters there was no significant effect because of high rainfall so that it inhibited the formation and growth of tubers. Keywords: Sweet Potatoes, Sukuh Varieties, Verticulture